Comparative Perspectives on Asset Forfeiture as a Mechanism for Recovering State Losses from Corruption - Maharani ‘Ainul Qolbi Fadhilah; Sugiharto (DE RECHT (Journal of Police and Law Enforcement), 2026)
Corruption is an extraordinary crime that continues to increase alongside development and technological advances, causing significant social and economic harm. Despite various legislative efforts, law enforcement still faces difficulties in tracing and recovering criminal proceeds. This study employs a normative legal method using a statute approach to Law Number 31 of 1999 on the Eradication of Corruption Crimes and its amendment, combined with a comparative approach examining asset forfeiture frameworks in the Netherlands, the United States, and the United Kingdom. It analyzes how the Asset Forfeiture Bill can facilitate the recovery of state losses arising from corruption under Articles 2 and 3 of the Corruption Eradication Law. The findings indicate that following Constitutional Court Decision Number 25/PUU-XIV/2016, which removed the word may from both provisions, state financial loss must be established as an actual and certain loss. This development strengthens the relevance of asset forfeiture as a mechanism that directly targets criminal proceeds without relying solely on a criminal conviction. The comparative analysis shows that the Netherlands is developing its framework through the Asset Recovery Guide, the United States implements the Civil Asset Forfeiture Reform Act through specialized institutions, and the United Kingdom applies the Proceeds of Crime Act 2002, enabling civil recovery without a criminal conviction. Accordingly, the Asset Forfeiture Bill should be enacted promptly by reinforcing its non-conviction-based in rem mechanism, inter-agency coordination, and international cooperation to enhance anti-corruption enforcement and restore public trust in Indonesia's legal system.